2002
DOI: 10.1046/j.1365-2842.2002.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disinfectants containing glutaraldehyde on bonding of a tri‐n‐butylborane initiated resin to dentine

Abstract: The purpose of this study was to evaluate the effects of disinfectants on the bond strength of resin to dentine. The surface of bovine dentine was exposed to formaldehyde (FA) aqueous solutions, glutaraldehyde (GA) aqueous solutions, 2-hydroxyethyl methacrylate aqueous solutions (HEMA), a commercially available dentine primer (Gluma CPS desensitizer, GLUMA), isotonic sodium chloride solution (IS), and distilled water (DW), and placed in a humidor (HU) at 37 degrees C, or non-stored (baseline). All dentine surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…A desensitizer containing 5% glutaraldehyde and 36% HEMA was beneficial for the MMA-TBB bonding system 29,75) . Formaldehyde did not markedly improve dentin bond strength when compared with glutaraldehyde 27) . As for cresol, eugenol, and phenol camphor, they negatively affected the bond strength of MMA-TBB bonding system to dentin, suggesting polymerization inhibition 26,76,77) .…”
Section: Effect Of Primers 1 Primers Containing Metal Ionsmentioning
confidence: 70%
See 3 more Smart Citations
“…A desensitizer containing 5% glutaraldehyde and 36% HEMA was beneficial for the MMA-TBB bonding system 29,75) . Formaldehyde did not markedly improve dentin bond strength when compared with glutaraldehyde 27) . As for cresol, eugenol, and phenol camphor, they negatively affected the bond strength of MMA-TBB bonding system to dentin, suggesting polymerization inhibition 26,76,77) .…”
Section: Effect Of Primers 1 Primers Containing Metal Ionsmentioning
confidence: 70%
“…Comparison of adherend materials between Groups 1-4 and Group 5, and between Group 7 and Group 8, indicated that adhesive bonding of metal to dentin was weaker than that of acrylic material to dentin 8,[25][26][27][28][29][30] . Tensile testing using dumbbell-shaped specimens revealed that conditioning with 10-3 conditioner for 30 s resulted in significantly lower bond strength than conditioning for 10 s only 31,32) .…”
Section: Evolution Of Mma/tbb Adhesive Resin and Its Subsequent Develmentioning
confidence: 98%
See 2 more Smart Citations
“…23 Baba et al evaluated the effects of disinfectants on the bond strength of resin to dentine and found that highest bond strengths was obtained with 5% glutaraldehyde after 168 h of exposure. 24 Our study is a pilot endeavor. Further studies on a larger sample and including more sterilizing agents are required to be undertaken to substantiate the more effective method of sterilization.…”
Section: Discussionmentioning
confidence: 99%